2016
DOI: 10.1186/s12864-016-2431-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic variation among Brazilian soybean cultivars through genome resequencing

Abstract: BackgroundSoybean [Glycine max (L.) Merrill] is one of the most important legumes cultivated worldwide, and Brazil is one of the main producers of this crop. Since the sequencing of its reference genome, interest in structural and allelic variations of cultivated and wild soybean germplasm has grown. To investigate the genetics of the Brazilian soybean germplasm, we selected soybean cultivars based on the year of commercialization, geographical region and maturity group and resequenced their genomes.ResultsWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 72 publications
(80 reference statements)
2
30
0
1
Order By: Relevance
“…Most DRGs are identified through quantitative trait locus mapping along with candidate gene cloning and linkage disequilibrium (LD) analysis using genomewide association studies. Fixation index (F st ) measured difference between two populations and was used to identify artificial selection events in population (Baute et al 2015;Maldonado Dos Santos et al 2016). Selection during domestication frequently leads to a differential loss of genetic diversity at specific genes in targeted genomic regions that control the trait subject to selection.…”
Section: Introductionmentioning
confidence: 99%
“…Most DRGs are identified through quantitative trait locus mapping along with candidate gene cloning and linkage disequilibrium (LD) analysis using genomewide association studies. Fixation index (F st ) measured difference between two populations and was used to identify artificial selection events in population (Baute et al 2015;Maldonado Dos Santos et al 2016). Selection during domestication frequently leads to a differential loss of genetic diversity at specific genes in targeted genomic regions that control the trait subject to selection.…”
Section: Introductionmentioning
confidence: 99%
“…Resequencing germplasm lines also enabled us to understand the spatial and temporal trends in diversity in released varieties of chickpea (Thudi et al, 2016a), cultivated and wild accessions of soybean (Lam et al, 2010;Zhou et al, 2015a), and a reference set of pigeonpea Table 1). Resequencing of 28 Brazilian soybean cultivars suggested that, despite the diversification of modern Brazilian cultivars, the soybean germplasm remains very narrow because of the large number of genome regions that exhibit low diversity (Maldonado dos Santos et al, 2016). In recent years, genotyping by sequencing, skim sequencing, diversity array technology (DArT)-seq and restriction site associated DNA sequencing approaches were also employed for developing high density genetic maps, refining the QTL mapping and identifying trait linked markers in legumes Kale et al, 2015;Contreras-Soto et al, 2017;Leamy et al, 2017;Valdisser et al, 2017).…”
Section: Sequencing and Genotypingmentioning
confidence: 99%
“…Two collections of soybeans were used: a first set of 727 accessions for which whole-genome sequencing had been previously released (Zhou et al 2015; Maldonado dos Santos et al 2016; Valliyodan et al2016; Fang et al 2017; Song et al 2017; Torkamaneh et al 2017) and a second set of 280 accession which were sequenced in this study. These were chosen to provide a more balanced representation of various soybean growing areas in the world.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, with increased fluctuations in climatic conditions, next-generation soybean cultivars must not only be higher yielding but also more resilient to multiple abiotic and biotic stresses (Djanaguiraman et al 2018). In the main soybean-growing areas of the world, soybean is an introduced crop and the foundational germplasm was very limited in its genetic diversity (Hyten et al 2006; Maldonado dos Santos 2016). Continued genetic improvement in soybeans will require a better understanding of the genetic and especially allelic diversity within worldwide resources (Qiu et al 2013).…”
Section: Introductionmentioning
confidence: 99%